Peninjauan Ulang Ketentuan Retaliasi sebagai Reformasi Aturan Penyelesaian Sengketa WTO - Hernowo, Tri (Indonesian Journal of International Law, 2008)
Remedies system in form of suspension of concession or retaliation under current WTO rules encounters some drawbacks for developing and least developed countries. Theoretical and empirical analysis suggests that retaliation barely exercise its rataliation right as the cose exceeds the benefit. Thus, the reformation of DSU rules is crucial, especially to amend Article 22 of Dispute Settlement Understanding.